Effectiveness of Prototype of Electrical Monitoring System Based on Internet of Thing (IOT) Technology for Residential Houses - AHAD, ROSNEE; Mohamad, Suhaimi; Sri Sumarwati (Research and Innovation in Technical and Vocational Education and Training, 2022)
The development of Internet of Things (IoT) technology is growing rapidly in line with the current needs of society. IoT technology can be used to facilitate various human affairs. However, it was found that wastage of electricity consumption often occurs among consumers. Researchers expect IoT technology to also make it easier for consumers to monitor electricity consumption for their homes to avoid wastage of electricity resulting in increased electricity bills. This paper presents effectiveness of prototype of electrical monitoring system based on internet of thing (IoT) technology for residential houses. This quantitative study uses experimental methods to test the effectiveness of a prototype electrical monitoring system based on IoT technology for residential homes. In this study, the researchers also identified the differences between the reading results using traditional methods (manual) and prototypes of electrical monitoring systems based on IoT technology for residential homes. The findings show that the prototype electrical monitoring system based on IoT technology has more accuracy and detail in analyzing energy consumption data as well as sensitivity by sending notifications about excess current found in residential wiring systems. The results of this study also show that the construction of this monitoring tool can also provide a new initiative in terms of data presentation to facilitate users to understand the data information presented because it is in the form of infographics (graphs) and in real-time. In conclusion, through the findings of this study, consumers can save money for electricity bill payments and save time to control electricity consumption only through mobile phones.